O NOVO CONSUMIDOR IDOSO: IDENTIFICAÇÃO DOS ATRIBUTOS VAREJISTAS RELEVANTES - Eduardo Garcia; Valdirene Mendes dos Santos; Monica Aparecida Schiavo (RAE: Revista de Administração de Empresas, 2013)
Both the world and Brazilian population are aging. There is a gap in academic studies on elderly consumer preference. This research focused on which retailer attributes are most important to maintain loyalty of this group of consumers. Two focus groups generated a list of 44 relevant retailer attributes, followed by a survey with 615 consumers over 60 years old. We found that the dimensions Service and Assortment Management (including management prices and products) explain 47% of the variability of loyalty in the sample. The results also pointed out that attributes related to internal and external structure of the store were not significant in the model, by means of structural equation modeling.